Effect of repeated bouts versus a single bout of moderate‐intensity exercise on postexercise inhibitory control. Issue 15 (9th August 2020) - Sugimoto, Takeshi; Suga, Tadashi; Tsukamoto, Hayato; Tomoo, Keigo; Dora, Kento; Hashimoto, Takeshi; Isaka, Tadao
Abstract: We previously demonstrated that duration of aerobic exercise plays an important role in improving cognitive inhibitory control (IC). Repeated bouts of aerobic exercise (R‐EX), which are performed with a rest interval, is a useful strategy in improving physical health parameters in similar manners to a single bout of aerobic exercise (S‐EX). However, whether R‐EX would be effective in improving IC remains unknown. This study compared the effect of R‐EX versus S‐EX of moderate‐intensity exercise on postexercise IC. Twenty healthy, young males performed both R‐EX and S‐EX in a crossover design. R‐EX consisted of two 20‐min moderate‐intensity bouts (60% of peak oxygen consumption) for 20 min, which were separated by a 20‐min rest interval. S‐EX consisted of a once‐off 40‐min moderate‐intensity bout without rest interval. To evaluate IC, the color‐word Stroop task was administered before exercise, immediately after exercise, and every 10 min during the 30‐min postexercise recovery period. The reverse‐Stroop interference score, which is a parameter of IC, significantly decreased immediately after both R‐EX and S‐EX compared with that before each exercise (both P s < 0.05). The degree of changes in IC following exercise did not differ between the two protocols. By contrast, the results of the present study showed that R‐EX may have more beneficial effects on cardiac and perceptual responses than S‐EX. Therefore, the present study determined that R‐EX changes postexercise IC similar to S‐EX. We suggest that R‐EX can be used as safe and effective exercise protocol to improve cognitive function in various populations. Abstract : Aerobic exercise improves postexercise cognitive function. Effective aerobic exercise protocols for improving cognitive function are poorly understood. A repeated bout protocol of aerobic exercise can be used as safe and effective exercise protocol to improve cognitive functioin.